A Study of Simultaneous Radioactive Gold and Cytostatic Therapy in the Treatment of Malignant Effusions - Varmas, K. D.; Schenck, P.; Lange, D. (Nuklearmedizin - NuclearMedicine, 1971)
I. A combination of radiogold and cytostatic drugs appears to give the best results in the treatment of malignant effusions.II. No correlation could be found between the type of tumour and the response to therapy.III. Asymptomatic patients seem to respond better to either forms of therapy.IV. The lasting relief may occur after 6–12 instillations of cytostatic drugs following 198Au therapy.V. The longest relief experienced in the present study lasted 2 years and 4 months and occured after a single application of 198Au.